Pengaruh Tarif, Kepercayaan dan E-Service Quality terhadap Kepuasan Pengguna Jasa Marpoken Delivery di Desa Gunung Tua - Maysaroh Hasibuan; Annio Indah Lestari Nasution; Nuri Aslami (Equivalent : Journal of Economic, Accounting and Management, 2024)
Abstract : The research aims to analyze the influence of tariffs, trust and e-service quality on user satisfaction with Marpoken Delivery services in Gunung Tua Jae Village, Panyabungan District, Mandailing Natal Regency. Quantitative research techniques were used in this research. The Gunung Tua Jae community served as the research sample, and non-probability sampling was used with a final sample size of 100 participants. Using questionnaires for data collection. SPSS was used to process the collected primary data. The research results show that first, with a substantial value of 0.020 to 0.05, tariffs have a good and significant effect on user satisfaction of Marpoken Delivery services in Gunung Tua Village. Second, with a substantial value of 0.019 to 0.05, trust has a positive and significant effect on user satisfaction of Marpoken Delivery services in Gunung Tua Jae Village. Third, E-Service Quality has a positive and significant effect on User Satisfaction of Marpoken Delivery services in Gunung Tua Jae Village with a significant value of 0.010 < 0.05. Fourth, simultaneously Tariff, Trust and E-Service Quality have a positive and significant effect on User Satisfaction with a significant value of 0.001 < 0.05. Abstrak : Penelitian bertujuan untuk menganalisis Pengaruh Tarif, Kepercayaan dan E-Service Quality Terhadap Kepuasan Pengguna Jasa Marpoken Delivery di Desa Gunung Tua Jae Kecamatan Panyabungan Kabupaten Mandailing Natal. Teknik penelitian kuantitatif digunakan dalam penelitian ini. Komunitas Gunung Tua Jae dijadikan sebagai sampel penelitian, dan pengambilan sampel non-probabilitas digunakan dengan ukuran sampel akhir 100 peserta. Menggunakan kuesioner untuk pengumpulan data. SPSS digunakan untuk mengolah data primer yang terkumpul.Hasil penelitian menunjukkan bahwa pertama, dengan nilai substansial 0,020 hingga 0,05, tarif berpengaruh baik dan signifikan terhadap kepuasan pengguna jasa Marpoken Delivery di Desa Gunung Tua. Kedua, dengan nilai substansial 0,019 hingga 0,05 kepercayaan berpengaruh positif dan signifikan terhadap kepuasan pengguna jasa Marpoken Delivery di Desa Gunung Tua Jae. Ketiga, E-Service Quality berpengaruh positif dan signifikan terhadap Kepuasan Pengguna jasa Marpoken Delivery di Desa Gunung Tua Jae dengan nilai signifikan 0,010 < 0,05. Keempat, secara simultan Tarif, Kepercayaan dan E-Service Quality berpengaruh positif dan signifikan terhadap Kepuasan Pengguna dengan nilai signifikan 0,001 < 0,05.